Cross-sectional descriptive study of lifestyle patterns of undergraduate medical students in a metropolitan Medical College - Patel, Pruthvi H.; Malgaonkar, Aniruddha A.; Kartikeyan, Sundaram (International Journal Of Community Medicine And Public Health, 2016)
Background: Studies report physical inactivity, mental stress, tobacco and alcohol use and unhealthy and untimely dietary habits in a sizeable proportion of medical students. This complete-enumeration, descriptive study was conducted in a metropolitan teaching hospital to assess the dietary habits and lifestyle of undergraduate medical students for designing specific health interventions based on the results of the study. Methods: After obtaining permissions and written informed consent, the participants were interviewed and also asked to self-rate their stress on a scale of zero to nine. Their heights and weights were recorded. Results: Lifestyle patterns of male (n=78) and female (n=94) respondents included vegetarianism (27.9%), skipping breakfast (13.95%), consuming four or more meals daily (61.63%), snacking between meals (43.02%), consumption of caffeinated soft drinks (38.37%) and tea/coffee (84.31%), sleeping for 6-8 hours daily (80.81%) with no gender difference in minimum and maximum sleep hours, lack of physical exercise (65.12%) or outdoor recreation (25.58%) and dominance of internet, television and computers as recreational tools. 60.46% studied only before exams. None were tobacco or alcohol habitual. 94.19% students had regular bowel habits and 68.03% had never suffered from constipation. Self-rated stress was often study-related and only 6.98% sought medical opinion for stress. Menstrual cycles in female respondents were irregular (14.89%), with mood changes (69.15%) and adversely affected studies (19.15%). Conclusions: The same recreational tools utilized by the respondents can be deployed for educational interventions to modify the identified risk factors in this study.